Developing Self-Learning Habit and Building Self Confidence by Integrating TBLT in Listening and Speaking Activities - Ayu Ida Savitri; Wiwiek Sundari (PAROLE: Journal of Linguistics and Education, 2021)
A common problem related to Teaching English as Foreign Language (TEFL) in an expanding circle country like Indonesia is students were accustomed to passively follow what the teacher told them to do. Task-Based Language Teaching (TBLT) is an effective method to let students develop their knowledge and creativity by learning the materials with their peers. It develops students’ self-learning habit that is beneficial for them to expand their knowledge, improve their competence and build their self-confidence as they were proud of their self-achievement. This research shows the integration of TBLT into listening and speaking class for second-grade students of State Vocational Senior Highschool, Central Java, majoring in electrical power engineering to fulfill their need as a technician with certain adaptations to suit the custom without decreasing its function and effectiveness